P07 Sensory impairments and cognitive ageing: findings from 11 european countries. (2nd September 2017) - Maharani, A; Pendleton, N; Tampubolon, G; Nazroo, J; Dawes, P
Abstract : Background: Sensory impairment (hearing and/or visual) and cognitive decline commonly occur in the elderly. Whether they are in fact associated, and whether sensory impairment might contribute to intellectual decline, has been a subject of a number of investigations during the past three decades. The purpose of this study was to assess in an older European population: (1) any independent association between single and dual sensory impairment (hearing and/or vision) and cognitive decline; (2) cognitive trajectories according to the pattern of sensory impairment. Methods: This study used data from the Survey of Health, Ageing and Retirement in Europe (SHARE) and English Longitudinal Study of Ageing (ELSA). We measured cognitive function by one key cognitive domain available in both surveys, namely episodic memory score (range 0–20). Sensory impairment was measured using self-reported hearing and vision quality in both SHARE and ELSA. Vision and hearing function in both surveys were each coded on a scale from 1 (excellent) to 5 (poor). We recoded the scores of hearing and vision function into two categories by combining the responses excellent, very good and good into `good' sensory function and collapsing fair and poor vision into `poor' sensory function. We defined sensory impairment as having poor sensory function and categorised it into three: no impairment, single impairment (vision or hearing), and dual impairment (vision and hearing). Results: Using growth curve analysis, we found that older adults with single and dual sensory impairment (hearing and/or vision) were able to recall fewer words than those with no sensory impairment in final model in all 11 European countries included in this study, where the potential confounders were included. The cognitive trajectories of older adults with no sensory impairment followed curvilinear shapes, while those of older adults with single and dual sensory impairments showed more precipitous pattern trajectory of cognitive decline after the age of 50 in both surveys. Being female, having attained a higher level of education, having paid job and being relatively wealthy, were associated with higher cognitive function in older age both in SHARE and ELSA. Conclusion: These findings demonstrate that hearing and/or vision impairment is a marker for risk of cognitive decline that could inform preventative interventions to maximise cognitive health and longevity. Further studies are needed to investigate how sensory markers could inform strategies to improve cognitive ageing, including hearing and vision rehabilitative intervention in combination with healthy ageing interventions to promote social engagement, physical activity and positive health behaviours.